دراسة تأثير بارامترات تصميم مصفوفة الهوائيات الخطية المتماثلة على اتجاه وصول الإشارات غير المترابطة المقدَّر باستخدام خوارزمية MUSIC - يونس معين; موسى شحادة; الصرن محمد (Latakia University Journal -Engineering Sciences Series, 2018)
تعتبر معالجة إشارة المصفوفة جزءاً هاماً في مجال معالجة الإشارة، وقد طُورت في السنوات الأخيرة بشكل كبير، إذ يمكن أن تطبَّق في مجالات مثل الكشف الراديوي، الاتصالات، السونار، الزلازل، علم الفلك، والطب البيولوجي. إنَّ بحث تقنية اتجاه الوصول Direction of Arrival (DOA) مهماً في معالجة إشارة المصفوفة خاصةً اتجاه الوصول لمصادر الإشارة المتعددة، وتقدير اتجاه مصادر الإشارات المترابطة. لقد حققت الخوارزميات المستخدمة في تقدير DOA خلال السنوات الماضية إنجازاً كبيراً، حيث تعتبر خوارزمية تصنيف الإشارة المتعددة MUltiple SIgnal Classification (MUSIC) من أقدم الخوارزميات والأكثر شيوعاً، وقد طوِّرت لتعطي إيجاد الاتجاه فائق الدقة عن طريق تقدير عدد الإشارات الواصلة وبالنتيجة اتجاهات وصولهم. Array signal processing is an important part in the field of signal processing, in recent years, it has been developed dramatically, it can be applied in such fields as radio detection, communication, sonar, earthquake, astronomy and biomedicine. Direction of Arrival (DOA) technology research is important in array signal processing, especially the direction of arrival with multiple signal sources and the estimation of direction of relevant signal sources. Over the past years, all algorithms used in DOA estimation have made great achievements, MUltiple SIgnal Classification (MUSIC) is considered one of the most common and oldest ones, which was developed to give super resolution direction finding, by estimating of number of arrived signals, hence their direction of arrival.